On the association between insurance deductibles and prevention behaviour: Evidence from the Swiss health system - Christophe Courbage; Christina Nicolas (Journal of Risk and Financial Management, 2021)
Many studies have attempted to investigate the drivers of preventive behaviour. This study contributes to this strand of literature by examining the association between higher insurance deductibles in the Swiss health system and preventive behaviour that allows for maintaining a good diet, exercising and limiting/abstaining from smoking and alcohol consumption. To conduct our study, we made use of the 2017 Swiss Health Survey and employed an ordered probit model with each prevention aspect as a dependant variable. Our results show that, except for alcohol consumption, higher insurance deductibles were significantly associated with higher behavioural prevention. Our study also highlighted how numerous other factors influenced prevention and offered some guidance for public policies to further incentivise prevention decisions.
Keywords: I12; I18; 330; health behaviour; health insurance; insurance deductibles; moral hazard